Sequence-Specific Protein Aggregation Generates Defined Protein Knockdowns in Plants . Issue 2 (4th May 2016) - Betti, Camilla; Vanhoutte, Isabelle; Coutuer, Silvie; De Rycke, Riet; Mishev, Kiril; Vuylsteke, Marnik; Aesaert, Stijn; Rombaut, Debbie; Gallardo, Rodrigo; De Smet, Frederik; Xu, Jie; Van Lijsebettens, Mieke; et al.
Abstract : A protein knockdown method based on expression of specific aggregation-prone peptides derived from the targeted proteins. Abstract: Protein aggregation is determined by short (5–15 amino acids) aggregation-prone regions (APRs) of the polypeptide sequence that self-associate in a specific manner to form β-structured inclusions. Here, we demonstrate that the sequence specificity of APRs can be exploited to selectively knock down proteins with different localization and function in plants. Synthetic aggregation-prone peptides derived from the APRs of either the negative regulators of the brassinosteroid (BR ) signaling, the glycogen synthase kinase 3/Arabidopsis SHAGGY-like kinases (GSK3/ASKs), or the starch-degrading enzyme α-glucan water dikinase were designed. Stable expression of the APRs in Arabidopsis ( Arabidopsis thaliana ) and maize ( Zea mays ) induced aggregation of the target proteins, giving rise to plants displaying constitutive BR responses and increased starch content, respectively. Overall, we show that the sequence specificity of APRs can be harnessed to generate aggregation-associated phenotypes in a targeted manner in different subcellular compartments. This study points toward the potential application of induced targeted aggregation as a useful tool to knock down protein functions in plants and, especially, to generate beneficial traits in crops.